ANALYSIS ON WRITTEN MATHEMATICAL COMMUNICATION SKILLS AT SYSTEM OF LINEAR EQUATIONS IN TWO VARIABLES (SLETV) MATERIAL VIEWED FROM STUDENT LEARNING STYLES - Pratiwi, Isnin Cahyo; Inganah, Siti; Putri, Octavina Rizky Utami (Study Program of Mathematics Education University of Muhammadiyah Malang, 2019)
This research was to describe students? mathematical communication skills based on their learning styles. This research was a descriptive research with qualitative approach. Data was obtained in three steps, namely written test on SLETV material, questionnaire on learning styles, and interviews. Research subject was eighth grade students. The procedure in this research began with the pre-field stage. At this stage, the research was designed, starting from observation and interviews with the teacher, as well as discussion with the supervisor. The second was the field stage, which was the stage for conducting research. The final stage was writing the report, which was the stage where researchers have conducted the research, processed and analyzed data that has been obtained from the research. Data collection techniques in this research were distributing questionnaire, giving test questions about SLETV, and conducting interviews to find out the students? mathematical communicationskills more specifically. The instruments in this study were questionnaire onlearning styles, test questions about SLETV, and interview guide sheets. Dataanalysis techniques in this research aimed to achieve data reduction by sorting out important answers from student results in the form of questionnaire, test, and interviews. Data presentation was in the form of narrative texts. Interviews were aligned with the test questions about SLETV. Finally, conclusions were formulated by describing each student?s written mathematical skill based on the 4 student learning styles. Based on the results, students with interpersonal learning style had the ability to learn better through friendship, students with self-expressive learning style had the ability to learn by paying more attention to the final results and tended to use unusual ways to find the best results, students with understanding learning style had the ability to see facts and remember large amounts of knowledge, ideas, theories, or concepts, while students with mastery learning style were able to write to the point and focus more on results.